Comparative Analysis Of The Level Of Knowledge Of Choosing Acne Skin Care Products On Beauty Students With Culinary Students - Allif Rizkia Amelita Putri; Agustin Eny Widhia; Achmadi Tofan Ali; Krisnawati Maria (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
Beauty problems are problems that are never discussed, one of which is acne, a skin problem that is often faced, especially by teenagers. Facial skin care is really needed to help overcome acne, ingredients that can overcome acne problems such as Glycolic acid, Salicylic Acid, Benzoyl Peroxide, and also Tea tree oil with its various different benefits. The aim of this research is to find out whether there is a comparison in the level of knowledge in choosing products for acne-prone skin between beauty and culinary students. The sample in this study used a purposive sampling method with the criteria of students experiencing acne skin problems. The results of the research show that the level of knowledge of students majoring in beauty and culinary is 71.89 and 63.39 respectively, this shows that students majoring in beauty have a higher level of knowledge about acne facial care than culinary majors in the sufficient category. The choice of products between students majoring in beauty and culinary was 48.85 and 41.47 respectively, this shows that students majoring in beauty products in choosing products for acne-prone skin were higher than culinary majors in the category of less in choosing products for acne-prone skin. . Then a comparison of the level of knowledge in choosing products for acne-prone skin between students majoring in Beauty and students majoring in Culinary with results of 70.43 and 60.75 respectively, this shows that students majoring in beauty are higher than students majoring in Culinary in the sufficient category. It can be concluded that students majoring in beauty and culinary are still quite lacking in choosing products for acne-prone skin which results in many students still having acne, even though when compared the level of knowledge of students majoring in beauty is slightly higher than students majoring in culinary beauty.